IMPLEMENTASI PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENINGKATKAN KESADARAN KEWARGANEGARAAN SISWA DI SMAN 1 SUNGAI TARAB - Rahmona, Maulana; Asril; Jamurin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of local wisdom-based learning in increasing students' civic awareness at SMAN 1 Sungai Tarab. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that learning has been implemented through cultural projects, traditional games, and mutual cooperation, which are related to civic values. Teachers play a strategic role in linking subject matter with local wisdom and encouraging active student involvement. Supporting factors for successful implementation include the Merdeka Curriculum policy and student enthusiasm. However, limited resources and difficulties in affective assessment are obstacles. In conclusion, local wisdom-based learning has proven effective in increasing students' civic awareness.